NILAI-NILAI PENDIDIKAN MULTIKULTURAL DALAM MEMBENTUK KARAKTER MODERASI BERAGAMA DI MAJELIS MAIYAH SINAU BARENG CAK NUN DAN KIAI KANJENG - M. Muizzuddin; Lestari, Puji (MIYAH : Jurnal Studi Islam, 2024)
Abstract: This study aims to describe and interpret the multicultural education values in Sinau Bareng sessions with Cak Nun and Kiai Kanjeng, as well as the process of instilling these values to foster religious moderation. A qualitative case study approach was employed, with data collected through participant observation, semi-structured interviews, and audiovisual documentation analysis. The data analysis utilized a descriptive method, involving data collection, organization, explanation, and interpretation. The findings indicate that the multicultural education values embodying religious moderation in Sinau Bareng include: (1) tolerance, (2) equality, (3) democracy, (4) justice, (5) harmony, (6) mutual understanding, (7) mutual assistance, and (8) deliberation. These values have a significant positive impact on daily life within the Majelis Maiyah community and society at large. However, as this study employs a qualitative case study approach, its findings are limited in generalizability. The results are specific to the context of Sinau Bareng with Cak Nun and Kiai Kanjeng and may not be directly applicable to other situations or groups. Keywords: Religious Moderation, Sinau Bareng, Tolerance, Democracy, Justice.